2008
DOI: 10.1007/s11136-008-9380-z
|View full text |Cite
|
Sign up to set email alerts
|

Clarifying quality of life assessment: do theoretical models capture the underlying cognitive processes?

Abstract: Objective To develop an analysis scheme capturing the cognitive processes underlying QoL assessment to increase our understanding on how to interpret responses to QoL items. Tourangeau et al.'s (The psychology of survey response, 2000) and Rapkin and Schwartz' (Health Qual Life Outcomes 2:14, 2004) cognitive process models form the basis for this analysis scheme. Methods We conducted think aloud interviews with six cancer patients prior to and following radiotherapy to elicit the cognitive processes underlying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 20 publications
0
28
0
1
Order By: Relevance
“…Some authors [54,55] state that patients focus more on the psychologic aspects (illness), while physicians focus more on the physical aspects (disease). An examination of such hypotheses could require the use of cognitive interviews [56] or other qualitative research approaches [57]. Our study indicates that in addition to the psychologic causes in the cognitive processes of the involved parties, the organizational conditions of treatment are also significant.…”
Section: Discussionmentioning
confidence: 82%
“…Some authors [54,55] state that patients focus more on the psychologic aspects (illness), while physicians focus more on the physical aspects (disease). An examination of such hypotheses could require the use of cognitive interviews [56] or other qualitative research approaches [57]. Our study indicates that in addition to the psychologic causes in the cognitive processes of the involved parties, the organizational conditions of treatment are also significant.…”
Section: Discussionmentioning
confidence: 82%
“…Another approach that also would elucidate the cognitive processes involved is cognitive interviewing. In this approach, patients are interviewed or asked to ''think aloud'' while answering the questionnaires to explore the cognitive processes they used [38,50,51]. The cognitive interviewing approach is under-explored in response shift research to date, and deserves further attention.…”
Section: Triangulationmentioning
confidence: 99%
“…Recent research by Tamineau-Bloem and colleagues [19] suggests that QOL appraisal changes not only between and within persons over time, but also within persons within a data collection time point. For example, in their cognitive interviewing study of 80 response processes of six cancer patients, Bloem and colleagues reported that patients compared themselves with other patients in one item and referred to their own functioning prior to cancer diagnosis in another [23]. These findings should be replicated on a larger, representative sample but do suggest, nonetheless, substantial changeability in appraisal states and that increased specificity may be important in characterizing QOL appraisal in patient-reported outcome measures.…”
Section: Discussionmentioning
confidence: 99%